2005
DOI: 10.1002/star.200400330
|View full text |Cite
|
Sign up to set email alerts
|

Water Redistribution and Structural Changes of Starch During Storage of a Gluten-free Bread

Abstract: The objective of the present work was to analyze molecular and supramolecular changes of bread starch and to relate bread firmness increase during storage with starch recrystallization and water hydration levels and migration in gluten-free bread. At the studied conditions starch was in the supercooled region of the state diagram, at a temperature between T g (glass transition temperature) and T m (melting temperature), feasible to crystallize. The crystalline degree during storage was followed by the intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 13 publications
1
59
0
6
Order By: Relevance
“…From all these contradictions, it can be seen that the behavior in the X-ray diffraction may depend on various factors including variety, agro-ecological conditions, pretreatment applied to the sample. Osella et al (2005) in a study of the effect of water content on the structural modifications of starches showed that for a water content below 23 %, starches develop a structure of type-A while those with a grade water more than 49 % develop type-B structure. Studies on the crystallization of sucrose show that crystallization is largely dependent on the concentration of sucrose in water and temperature (Van Hook, 1959).…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…From all these contradictions, it can be seen that the behavior in the X-ray diffraction may depend on various factors including variety, agro-ecological conditions, pretreatment applied to the sample. Osella et al (2005) in a study of the effect of water content on the structural modifications of starches showed that for a water content below 23 %, starches develop a structure of type-A while those with a grade water more than 49 % develop type-B structure. Studies on the crystallization of sucrose show that crystallization is largely dependent on the concentration of sucrose in water and temperature (Van Hook, 1959).…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…As an example of the applicability of phase/state diagrams in the prediction of food quality aspects, Fig. 6 shows a state diagram illustrating the evolution of two starch-containing dough systems during bread making (from dough A to final product) [143]. T s1 and T s2 represent the gelatinization temperatures for two formulations containing corn starch and other biopolymers.…”
Section: Cereal Productsmentioning
confidence: 99%
“…• Analysis of the increasing intensities and areas of peaks in X-ray diffraction (XRD) patterns is also possible [143,212]. XRD is a practical technique for identifying crystal forms and for following or characterizing rates of crystallization of components, especially when systems are complicated, such as systems with several crystallizing components.…”
Section: Sugar Crystallizationmentioning
confidence: 99%
“…Some of the detrimental effects of wheat substitution on bread making include reduction in loaf volume, crumb structure, product shelf life, and impairment of sensory qualities such as appearance, texture, flavor, and mouth feeling (Shittu et al, 2007;Houben et al, 2012). Osella et al (2005) reported that gluten-free bread produced with different starches often ages rapidly.…”
Section: Challenges Of 40% Cassava Inclusion In Bread Policymentioning
confidence: 99%
“…Bread has been described as an unstable elastic solid foam containing a continuous phase of elastic network of cross linking gluten molecules and starch polymer, mostly amylase, and a discontinuous phase of entrapped, partially gelatinized, swollen and deformed starch granules (Osella et al, 2005;Gray and BeMiller, 2003). Bread is normally made from wheat flour dough that is cultured with yeast, allowed to rise, and baked (Komlaga et al, 2012).…”
Section: Introductionmentioning
confidence: 99%